Host reaction to vaginally inserted collagen containing polypropylene implants in sheep - Feola, Andrew; Endo, Masayuki; Urbankova, Iva; Vlacil, Jaromír; Deprest, Thomas; Bettin, Samantha; Klosterhalfen, Bernd; Deprest, Jan (American journal of obstetrics and gynecology, 2015)
OBJECTIVE: We aimed to characterize the effect of vaginal or abdominal mesh insertion and of different collagen augmentation of polypropylene mesh in a sheep model. Outcome measures were passive and active biomechanical properties and semiquantitative morphometry. STUDY DESIGN: Forty-two Texel sheep were used: 6 were nonimplanted controls (n = 6), the rest were implanted with polypropylene mesh (n = 12; Avaulta Solo; Bard Medical, Covington, GA) or collagen-coated meshes: Avaulta Plus (n = 12; Bard Medical) and Ugytex (n = 12; Sofradim International, Trevoux, France). Through a single incision, the rectovaginal septum was dissected and a 35 × 35-mm mesh was sutured to the underlying tissues. Abdominally, a 50 × 50-mm mesh was laid over a primarily sutured full thickness 40-mm longitudinal incisional defect. Animals were explanted after 60 or 180 days (n = 6 per group). Outcome measures were passive biomechanics by biaxial tensiometry, active contractility of vaginal explants, and histologic evidence. RESULTS: Vaginal explants were 2.4 times stiffer compared with native vaginal tissue (P < .001), but without differences in comfort zone stiffness or slope of the load-elongation in the physiologic range between the products that were tested. Collagen coating was associated with a 16-fold reduction in contractile force at 180 days, compared with native vaginal tissue, both for Avaulta Plus (P = .032) and Ugytex (P = .015). Abdominal explants were 1.3-times stiffer compared with native abdominal wall tissue (P < .001) and were 1.9-times stiffer compared with vaginal explants. CONCLUSION: Vaginal mesh implantation yields less stiff explants compared with abdominal explants. Vaginal mesh implantation also alters the passive and active biomechanical properties compared with native vaginal tissues. Collagen matrices did not reduce the number of graft-related complications.
Keywords: Abdominal Wall; pooperační komplikace; vagina; Collagen; Female; polypropyleny; Polypropylenes; Sheep; ženské pohlaví; břišní stěna; kolagen; Vagina; biomechanika; ovce; zvířata; Biomechanical Phenomena; Animals; Surgical Mesh; chirurgické síťky; Postoperative Complications